DAYA TERIMA DAN KANDUNGAN KALSIUM ZAT BESI STICK SUBSTITUSI TEPUNG IKAN TERI DENGAN TEPUNG TEMPE - sitti ria rowa (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
ABSTRACKSchool-age children (7-9) years are experiencing a growth phase. Growth of children during this period includes weight gain, height, and development in the vital organs of the child, so that adequate nutrition is needed to support the growth and development of children. One of the nutrients needed for growth is calcium and iron. The aim of this study are to determine the acceptability and analysis of calcium and iron in the substitute sticks of white anchovy flour and tempe flour. This type of research is Pre Experimental with 'one group design' research design. Receiving power was assessed based on the hedonic test of 35 panelists. The best received power results are then carried out laboratory tests to analyze calcium and iron content. Data is presented in the form of frequency distribution tables and narratives.The results showed that the best panelists received a stick of 10% white anchovy flour substitution and 20% tempe flour. Color panelists 54.3%, texture aspects 68.6%, aspects 42.9%. The results of the calisum analysis were 329.23 mg/kg and iron liked the aspect aspect 206.16 mg/kg. The conclusion is sticks with a concentration of 10% white anchovy and 20% tempe flour are most preferred by panelists in terms of color, texture, aroma and taste.